Digest: Ecology and signal structure drive the evolution of synchronous displays in fiddler crabs. (3rd December 2019) - Khodaei, Lucas
Abstract: Behaviors are often influenced by both ecology and genetics. Perez et al. tested whether display patterns and the ecology of different species of fiddler crabs influence synchronous waving and whether this a phylogenetic phenomenon. They found that there was no phylogenetic signal in wave display synchronicity, and suggested that signal structure, microhabitat complexity, and different mating systems might instead be the cause. These results support the non‐phylogenetic nature of synchronicity that can be observed across animal taxa.